Minding the gap: a sex difference in young infants’ mental rotation through thirty degrees of arc - Moore, David S.; Moore, Dawn Michele; Johnson, Scott P. (Frontiers in Psychology, 2024)
Mental rotation (MR) is an important feature of spatial cognition invoking mental imagery of an object’s appearance when viewed from a new orientation. Prior studies have revealed evidence of MR in infants, including a sex difference similar to that detected in older populations. Some of these studies used visual habituation methods whereby infants were familiarized with an object rotating through a 240° angle, followed by test trials showing either the habituation object or a mirror image object rotating through the previously unseen 120° angle. Significantly longer looking at either of these objects was taken to reflect infants’ ability to recognize the habituation object even when seen from a novel viewpoint, suggesting the capacity for MR. However, these infants’ responses could, in theory, be explained with reference to perceptual discrimination rather than MR, because the views of the habituation and test objects were very similar in some video frames. In the current study, we observed a diverse population of 5-month-olds (24 females, 24 males) for evidence of MR through 30° of arc. In this more challenging test, our stimuli left a 30° gap angle between critical video frames representing the habituation and test objects. Consistent with earlier reports, we found that relative to female infants, male infants looked significantly longer at the mirror image test stimulus immediately following habituation. These results add to an emerging consensus that some young infants are capable of MR, and that male and female infants on average behave differently in this type of MR task.